The Representation of Women’s Resilience and the Construction of Moral Values in the Novel Soe Isabel by M. Tiyasaa: Representasi Ketegaran Perempuan dan Konstruksi Nilai Moral dalam Novel Soe Isabel Karya M. Tiyasaa - Wa Ode Risnayanti; Aris Badara; Yunus (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2026)
This study aims to describe the representation of women’s resilience and analyze the construction of moral values in the novel Soe Isabel. The research employs a descriptive qualitative design using a moral approach and the perspective of female character representation. The data source is the novel Soe Isabel, published by Yrama Widya in 2019, while the data consist of words, phrases, sentences, dialogues, and narrative passages that reflect women’s resilience and moral values. Data were collected through reading, marking, and note-taking techniques using data cards as research instruments. The data were analyzed through identification, reduction, classification, presentation, interpretation, and conclusion drawing. The findings reveal that women’s resilience is represented through the protagonist’s endurance in facing family loss, her ability to cope with loneliness, her determination in making life choices and maintaining personal beliefs, and her willingness to establish empathetic social relationships. Moral values are constructed through three major forms of relationships: the religious relationship between humans and God, the personal relationship with oneself, and the social relationship with others. The study concludes that morality in Soe Isabel is not presented merely as a set of normative teachings but as a process of self-formation shaped by experiences of grief, acceptance, perseverance, and compassion. This research contributes to the development of Indonesian literary studies by integrating moral value analysis with the representation of women’s resilience, thereby broadening the understanding of morality as a narrative process and a gendered experience in literary works.